Molecular characteristics of Cryptosporidium spp. in human cases in five Finnish hospital districts during 2021 : first findings of Cryptosporidium mortiferum (Cryptosporidium chipmunk genotype I) in Finland - Häkkänen, Tessa; Rimhanen-Finne, Ruska; Antikainen, Jenni; Ruotsalainen, Eeva; Vainio, Anni (ELSEVIER SCI IRELAND LTD, 2024)
The aims of the study were to characterise the distribution of Cryptosporidium spp. and subtypes causing infections in Finland during 2021. This was carried out with 60 clinical samples from the hospital districts of Helsinki and Uusimaa, Vaasa, Kymenlaakso, South Karelia, and Central Finland, as well as with Finnish Infectious Diseases Register (FIDR) data. Additionally, the study aimed to explore the potential exposures related to Cryptosporidium mortiferum (Cryptosporidium chipmunk genotype I) infections via interview. Species identification was carried out with quantitative real-time PCR (qPCR) and 18S sequencing. Further typing was performed with gp60 subtyping. Over 70% of the samples were identified as Cryptosporidium parvum and 20% as C. mortiferum, which had not been identified in Finland before. Two cases of Cryptosporidium hominis were identified from patients reported to have travelled outside Europe. The C. parvum subtype IIaA15G2R1 and the C. mortiferum subtype XIVaA20G2T1 were the most common subtypes identified. The interviewed C. mortiferum cases did not report shared exposures such as contact with wild rodents. In conclusion, C. parvum and C. mortiferum were the major causes of cryptosporidiosis in the five studied Finnish hospital districts. Peer reviewed